Study Of Solution Processed Cu(In, Ga)S2 By Post-Deposition Treatments. Issue 1670 (7th July 2014) - Armstrong, J.C.; Cui, J.B.; Chen, T.P.
ABSTRACT: In this study, we have investigated various approaches to improve CIGS solar cells after thin film deposition. CIGS devices have been fabricated by a hydrazine solution based process. Post-deposition treatments by sulfurization were studied with focuses on the change of material structures and physical properties. Sulfurization has shown to increase grain size and band gap of the absorber layers at higher temperatures. This property change has shown a direct impact on open circuit voltage of the solar cell devices. Through these post-deposition processes, improved quality of CIGS materials can be obtained and the associated solar cell devices show better performance.